2021
DOI: 10.1002/micr.30794
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional markers for predicting lower extremity free tissue transfer outcomes in the chronic wound population

Abstract: Background Optimizing nutritional status is critical to maximize flap success and healing. Prealbumin and albumin have been utilized as easily obtained proxies for overall nutritional status. The aim of this study was to investigate whether these markers are correlated with healing time and overall flap healing after lower extremity (LE) free tissue transfer (FTT) in the chronic wound population. Methods A retrospective review of LE chronic wound FTT patients treated by a single surgeon at our institution from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Increased BMI, history of DM, and history of more than 2 spinal surgeries, which have been identified in other single-institution studies of a similar patient population, were not associated with an increased rate of infection or reoperation in our study 4,5 . Nutritional status is critical to proper wound healing; surgical trauma induces hypermetabolism, whereas wound healing requires significant protein synthesis for proper formation of granulation tissue and anabolic pathways 20–23 . Specific to surgical wounds of the spine, previous studies have identified low prealbumin levels (<20 mg/dL) as an independent risk factor for postoperative infection as well as reoperation and increased length of stay after reconstruction 4,24 .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Increased BMI, history of DM, and history of more than 2 spinal surgeries, which have been identified in other single-institution studies of a similar patient population, were not associated with an increased rate of infection or reoperation in our study 4,5 . Nutritional status is critical to proper wound healing; surgical trauma induces hypermetabolism, whereas wound healing requires significant protein synthesis for proper formation of granulation tissue and anabolic pathways 20–23 . Specific to surgical wounds of the spine, previous studies have identified low prealbumin levels (<20 mg/dL) as an independent risk factor for postoperative infection as well as reoperation and increased length of stay after reconstruction 4,24 .…”
Section: Discussionsupporting
confidence: 65%
“…4,5 Nutritional status is critical to proper wound healing; surgical trauma induces hypermetabolism, whereas wound healing requires significant protein synthesis for proper formation of granulation tissue and anabolic pathways. [20][21][22][23] Specific to surgical wounds of the spine, previous studies have identified low prealbumin levels (<20 mg/dL) as an independent risk factor for postoperative infection as well as reoperation and increased length of stay after reconstruction. 4,24 Our investigation identified an association between prealbumin and seroma but not between other postoperative complications including infection or dehiscence.…”
Section: Discussionmentioning
confidence: 99%